Drug Therapy Problems Identified by Pharmacists Through Comprehensive Medication Management Following Hospital Discharge. (June 2017) - Westberg, Sarah M.; Derr, Sarah K.; Weinhandl, Eric D.; Adam, Terrence J.; Brummel, Amanda R.; Lahti, Joseph; Reidt, Shannon L.; Sick, Brian T.; Skiermont, Kyle F.; St. Peter, Wendy L.
Background: Pharmacists influence health care outcomes through the identification and resolution of drug therapy problems (DTPs).Objective: The objectives of this study were to describe number, type, and severity of DTPs based on clinical significance and likelihood of harm in patients transitioning from hospital to home as assessed during a comprehensive medication management (CMM) visit with a pharmacist. Secondary objectives were to assess intrarater reliability in severity ratings and assess likelihood of harm for adverse drug reactions (ADR) by drug classes.Methods: Retrospective review of 408 patients having a face-to-face, telephonic, or virtual CMM visit within the Fairview Health System. Teams of 3 investigators reviewed each DTP from the electronic medical record for each of the 408 patients and assigned a severity score (0-10) for clinical significance and likelihood of harm.Main Results: The highest severity DTP classes were adherence and ADR. The lowest severity DTP class was unnecessary drug therapy. An average of 2.5 DTPs was found per patient at the index CMM visit following hospital discharge. The most common DTP classes were needs additional therapy and dose too low. There were statistically significant differences in DTP severity scoring between reviewer types, though differences were <5%. Drug classes with the highest severity ADR included diabetes, cardiovascular, and anticoagulant/antiplatelet agents.Conclusions: The DTP severity ratings indicated that reviewers found ADR and adherence DTPs were potentially the most severe. There were differences in DTP ratings between reviewer types, though clinical significance of these differences is unclear.